Navigating Project Change: A Comprehensive Review of Change Management Strategies and Practices - Zangana, Hewa Majeed; Bazeed, Sameer Mohammed Salih; Ali, Natheer Yaseen; Abdullah, Dilovan Taha (Indonesian Journal of Education and Social Sciences, 2024)
Project change management is a critical aspect of project management that ensures successful adaptation to evolving circumstances, requirements, and stakeholder expectations. This review paper explores various dimensions of change management within project environments, including key concepts, strategies, challenges, and future directions. Drawing upon a diverse range of literature, case studies, and examples, we examine the importance of change management in driving project success. From proactive change planning to stakeholder engagement, communication, and overcoming resistance, effective change management practices are essential for navigating the complexities of project change. Despite inherent challenges and limitations, organizations have the opportunity to leverage emerging trends such as technology integration, agile methodologies, sustainability, and cultural change to enhance their change management capabilities and drive sustainable project outcomes. As organizations continue to evolve in a dynamic world, project managers must embrace change as a constant aspect of project management, adopting proactive, adaptive, and strategic approaches to enhance resilience and drive positive change. This review paper provides valuable insights and guidance for practitioners seeking to strengthen their change management capabilities and achieve project success.